Islamic modernities in Southeast Asia exploring Indonesian popular and visual culture - Schmidt, Leonie (Asian cultural studies: transnational and dialogic approaches, 2017)
Demonstrates how new Islamic modernities are being negotiated and constructed through popular and visual culture in Indonesia.